Spatial characteristics and removal of dissolved black carbon in the western Arctic Ocean and Bering Sea. (1st July 2021) - Fang, Ziming; Yang, Weifeng; Stubbins, Aron; Chen, Min; Li, Junjie; Jia, Renming; Li, Qi; Zhu, Jing; Wang, Bo
Highlights: Dissolved black carbon (DBC) was first determined in the western Arctic Ocean and Bering Sea. Freshwater dominants the spatial pattern of DBC, river water and sea-ice meltwater show contrasting effect on DBC content. The shelves represent the main removal sites of riverine DBC and determine DBC reaching the open oceans. Abstract: In the Arctic, large amounts of black carbon (BC) are released into river water and transported to the oceans as dissolved BC (DBC). However, the cycling and fate of DBC in the ocean is poorly understood. Here, DBC, dissolved organic carbon (DOC), absorbance, and δ 18 O were analyzed to examine the spatial characteristics and removal of DBC in the western Arctic Ocean and the Bering Sea during the boreal summer. DBC concentrations ranged from 0.67 to 4.18 μmol-C L −1 . In the sea-ice free regions, high DBC and DOC concentrations and a 254 values corresponded to high δ 18 O-derived meteoric water contents, indicating that river discharge dominated their spatial patterns. By contrast, sea-ice meltwater (SIM) appeared to dilute DBC and DOC in SIM impacted waters (SIM > 3.5%). The departure of DBC from conservative mixing lines suggested that 47–84% of riverine DBC was removed over the shelves with 7–23% transported to the upper Canada Basin. These results suggest that shelf regions are crucial sites for riverine DBC removal that modulate the delivery of DBC to the open Arctic Ocean.